2011
DOI: 10.1007/s10482-011-9605-y
|View full text |Cite
|
Sign up to set email alerts
|

Yeast communities associated with artisanal mezcal fermentations from Agave salmiana

Abstract: The aims of this work were to characterize the fermentation process of mezcal from San Luis Potosi, México and identify the yeasts present in the fermentation using molecular culture-dependent methods (RFLP of the 5.8S-ITS and sequencing of the D1/D2 domain) and also by using a culture-independent method (DGGE). The alcoholic fermentations of two separate musts obtained from Agave salmiana were analyzed. Sugar, ethanol and major volatile compounds concentrations were higher in the first fermentation, which sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 48 publications
0
29
1
Order By: Relevance
“…This association with fermented dairy beverages, a consequence of its capacity to use the milk sugar lactose as a carbon source, has led to inclusion of K. marxianus on GRAS (FDA) and QPS (EU) lists of safe micro-organism for use in foods (Lane and Morrissey, 2010 ; Ricci et al, 2017 ). The yeast is also regularly isolated from non-dairy environments (e.g., decaying fruit) and is part of the natural flora involved in production of Agave -based alcoholic beverages such as tequila and mezcal (Lappe-Oliveras et al, 2008 ; Verdugo Valdez et al, 2011 ). In the latter case, the production of enzymes that degrade plant fructans to simpler sugars (inulinases) undoubtedly contributes to its growth in this environment (Arrizon et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…This association with fermented dairy beverages, a consequence of its capacity to use the milk sugar lactose as a carbon source, has led to inclusion of K. marxianus on GRAS (FDA) and QPS (EU) lists of safe micro-organism for use in foods (Lane and Morrissey, 2010 ; Ricci et al, 2017 ). The yeast is also regularly isolated from non-dairy environments (e.g., decaying fruit) and is part of the natural flora involved in production of Agave -based alcoholic beverages such as tequila and mezcal (Lappe-Oliveras et al, 2008 ; Verdugo Valdez et al, 2011 ). In the latter case, the production of enzymes that degrade plant fructans to simpler sugars (inulinases) undoubtedly contributes to its growth in this environment (Arrizon et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…T. delbrueckii is also naturally associated with several other human bioprocesses, ranging from food fermentations of silage, cocoa [29], [30], olive [31] or cucumber [32], [33], to distilled and traditional fermented beverage production including mezcal [34], colonche [35], tequila [36], cider [37], strawberry tree fruits juice [38], sugarcane juice [39], [40] and kefir [41]. T. delbrueckii is a frequent component of dairy products' microflora, either as desirable ferment for traditional cheeses [42] and fermented milk [43], or as spoilage yeast [44], [45].…”
Section: Introductionmentioning
confidence: 99%
“…They were unable to isolate S. cerevisiae, probably because of the saponins contained on the juice. Conversely, Verdugo et al (2011) [27] isolated and identified S. cerevisiae strains during the spontaneous fermentation of A. salmiana juice, although they did not mention if these S. cerevisiae strains are able to ferment when grown on this agave juice. The results obtained in this work may be explained by the fact that both Agave species (A. salmiana and A. durangensis) display the highest saponin content ( Table 2).…”
Section: Discussionmentioning
confidence: 99%